Surgery Strategies for Gastric Cancer With Liver Metastasis - Luo, Zai; Rong, Zeyin; Huang, Chen (Frontiers in Oncology, 2019)
Gastric cancer with liver metastasis is defined as advanced gastric cancer and remains one of the deadliest diseases with poor prognosis. Approximately 4–14% of patients with gastric cancers presented with liver metastases at the initial diagnosis. Owing to its incurability, first-line treatment for gastric cancer with liver metastases is systematic chemotherapy, whereas surgery is usually performed to alleviate severe gastrointestinal symptoms. However, continuously emerging retrospective studies confirmed the role of surgery in gastric cancer with liver metastases and showed significantly improved survival rate in patients assigned to a group of surgery with or without chemotherapy. Therefore, more and more convincing data that resulted from prospective randomized clinical trials is in need to clarify the surgery strategies in patients with gastric cancer with liver metastasis.